2018
DOI: 10.3168/jds.2017-13463
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Cronobacter malonaticus cells and inhibition of its biofilm formation exposed to hydrogen peroxide stress

Abstract: Presence of Cronobacter malonaticus in powdered infant formula (PIF) poses a high risk to infant and public health. Cronobacter malonaticus has been widely distributed in food and food processing environments, and the true origin of C. malonaticus in PIF is poorly understood. Control and prevention of C. malonaticus is necessary for achieving microbial safety of PIF. However, little information about decontamination of C. malonaticus is available. In this study, effects of hydrogen peroxide on inactivation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Based on the screening of random mutant library in C. malonaticus, five factors were identified to involve in tolerance to osmotic stress in previous study (Zhang et al 2018): KefA (potassium efflux protein), YqjF (inner membrane protein), peptidylprolyl isomerase, Cys-tRNA(Pro)/CystRNA(Cys) deacylase and oligo galacturonate lyase. We also demonstrated that outer membrane protein W (OmpW) contributed to the osmotic tolerance in C. sakazakii by gene knockout in our previous study (Ye et al 2018).…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…Based on the screening of random mutant library in C. malonaticus, five factors were identified to involve in tolerance to osmotic stress in previous study (Zhang et al 2018): KefA (potassium efflux protein), YqjF (inner membrane protein), peptidylprolyl isomerase, Cys-tRNA(Pro)/CystRNA(Cys) deacylase and oligo galacturonate lyase. We also demonstrated that outer membrane protein W (OmpW) contributed to the osmotic tolerance in C. sakazakii by gene knockout in our previous study (Ye et al 2018).…”
Section: Introductionmentioning
confidence: 51%
“…We also demonstrated that outer membrane protein W (OmpW) contributed to the osmotic tolerance in C. sakazakii by gene knockout in our previous study (Ye et al . 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) (Data S2). As an internal control of the method of biofilm formation, we used the bacterium Cronobacter malonaticus 161007/29 (C. malonaticus 161007/29), which is well known to form biofilm on various surfaces (Ye et al, 2018). Overall, the mean OD 570 for C. malonaticus 161007/29 was significantly higher than the mean OD 570 for Ter-positive (Te-R) and Ter-negative cells (control) (**** P < 0.0001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ) is a well-studied sanitizer for inactivate foodborne pathogens. In addition, Ye et al (2018) determined the inhibitory effects of H 2 O 2 on C. malonaticus cells and its biofilm formation. However, information about factors involved in oxidative tolerance in C. malonaticus is largely unknown.…”
Section: Introductionmentioning
confidence: 99%